Prevalence and genetic diversity of gastroenteritis viruses in hospitalized children < 5 years of age in Maharashtra state, Western India, 2017–2019. Issue 8 (24th May 2021) - Gopalkrishna, Varanasi; Joshi, Madhuri S.; Chavan, Nutan A.; Shinde, Manohar S.; Walimbe, Atul M.; Sawant, Pradeep M.; Kalrao, Vijay R.; Dhongade, Ram K.; Bavdekar, Ashish R.
Abstract: Four gastroenteritis viruses were responsible for 54% of the acute gastroenteritis (AGE) cases in children hospitalized between May 2017 and December 2019 in Pune city of Maharashtra state, Western India. The majority (79%) of the children were <2 years of age. The prevalence of Rotavirus A (RVA) was 30.5% followed by 14.3% for norovirus, 8.4% for adenovirus, and 5.5% for astrovirus. The severity of the disease was highest in patients with coinfections compared with the patients with a single infection or negative for all ( p = 0.024). Genotyping analysis showed that the majority of the RVA‐positive samples (66%) could be typed as G3P[8], 63.6% of the norovirus as GII.4 Sydney [P16], 44% of the adenovirus as type 41%, and 56.2% of the astrovirus as astrovirus type 1. The almost equivalent prevalence of rotavirus and nonrotaviruses and acute gastroenteritis (AGE) cases without known etiology in around 46% of the cases was noted in the present study. Our data highlight that after the recent inclusion of rotavirus vaccines as a part of the National Immunization schedule in India, conducting extensive AGE surveillance in children should include nonrotaviruses such as norovirus. Highlights: Four gastroenteritis viruses were responsible for 54% of the acute gastroenteritis (AGE) cases in children, Western India. Significant decline in Rotavirus A (RVA) AGE cases in children age <5 years. Dominance of RVA G3P[8] and decline of G1P[8] & G2P[4] genotype strains. Highly transmissible GII.P16‐GII.4 genotype strains in 63.6% of norovirus infections. Clinical severity of the disease showed, no correlation with regard to different RVA genotypes or norovirus strains.